Studying interaction of Moist-Chilling and gibberellic acid on germination of Fritillaria imperialis - Z. Aghababnejad; A. Abbasi Surki; P. Tahmasebi (علوم و فناوری بذر ایران)
There are several limitations in reproduction of Fritilaria imperilais using tissue tissue culture, lamination and bulb division. In this study, we designed a factorial experiment in a randomized complete block for evaluating the effects of several treatments such as cold duration (0, 4 and 8 weeks), concentrations of GA3 (0, 250 and 500 ppm) and application time in three steps (before, during and after stratification). The results showed that the seeds were highly germinated using 8 weeks stratification compares to others. Moreover, 500ppm gibberllin before stratifications significantly increased percentage of germination, Vigor Index Ι, length of radical, plumule, seedling and seedling dry weight, however significantly decreased E50. The results also showed that increasing the GA3 from 250 to 500ppm had significantly positive effect on all the traits. This study indicates that 8 weeks stratification along with 500ppm is more likely to increase the germination index of Fritilaria imperilais.